Implementation of Differential Scanning Calorimetry when Studying Polymerization of Compounds Based on Glycolic Acid Ether - Babkina O. V.; Vaytulevich (Vaitulevich) E. A. Elena Anatolievna; Gordeeva O. B. Olga Borisovna; Sarycheva G. A.; Nemoykina A. L. Anna Leonidovna; Alekseenko K. V. Kira Viktorovna (2015, 2015)
Title screen